(untitled) (Ameghiniana, 2013)
The morphological analysis of specimens referable to the genus Platipygus De Loriol has permitted to clarify its systematic position, being assigned here to the Family Faujasiidae Lambert. The diagnosis of the family is extended in order to include a feature present in this genus: Platipygus posthumus (Ortmann) are described and illustrated, with comments on their morphological variation together with their geographic and stratigraphic distribution. Finally, the mode of life of the species is also analyzed.